THE RELATIONSHIP AMONG HBA1C, LOW-DENSITY LIPOPROTEIN (LDL) CHOLESTEROL, AND SYSTOLIC BLOOD PRESSURE IN PATIENTS WITH DIABETES MELLITUS - Ni Made Juniari; I Wayan Sukawana; I Gusti Made Andika Putra (Poltekkes Kemenkes Jakarta III, 2026)
Diabetes mellitus is a chronic disease often accompanied by cardiovascular complications, one of which is hypertension. Controlling HbA1c and LDL cholesterol levels is a crucial component of diabetes mellitus management, aiming to reduce the risk of these complications. This study aimed to analyze the association between HbA1c control and LDL cholesterol control with systolic blood pressure control in diabetes mellitus patients at the Tejakula II Community Health Center. This study used an observational analytical design with a cross-sectional approach. The subjects were registered Diabetes Mellitus patients receiving services at the Tejakula II Community Health Center. The sample size of this research was 47 participants. Data on HbA1C, LDL cholesterol, and systolic blood pressure were obtained from patient medical records. Data were analyzed bivariately using appropriate statistical tests and odds ratio calculations. The results showed that HbA1C and LDL cholesterol control were not significantly associated with systolic blood pressure control (p > 0.05). The model explained 13.4% of the variation in systolic blood pressure control (Nagelkerke R² = 0,134). Although the odds ratios suggested a tendency toward a higher risk of uncontrolled systolic blood pressure among patients with uncontrolled HbA1C and LDL levels, these associations were not statistically significant. However, patients with uncontrolled HbA1C and LDL cholesterol levels had a higher risk of developing uncontrolled systolic blood pressure. Diabetes Mellitus management needs to be carried out comprehensively and multifactorially in primary health care facilities.